Different Parameters in Coconut (Cocos Nucifera) Wine Fermentation - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2016)
Coconut (Cocos Nucifera) juice is an ancient tropical beverage whose popularity on the international market has been continuously increasing in recent years. The coconut (Cocos nucifera L.) is an important fruit tree in the tropical regions and the fruit can be made into a variety of foods and beverages. Coconut water is the clear liquid inside young coconuts. Coconut water (coconut liquid endosperm) is one of the world’s most versatile natural products. This refreshing beverage is consumed worldwide as it is nutritious and beneficial for health. An attempt explored a wine fermentation from coconut juice by examining the effect of different parameters such as soluble solid content (14.0oBrix, 14.5oBrix, 15.0 oBrix, 15.5 oBrix), fermentation temperature (28.5oC, 29oC, 29.5oC, 30.0oC), yeast Sacchromyces cerevisiae ratio (1.0%, 1.5%, 2.0%, 2.5%) to coconut wine quality. Our results proved that 15.0oBrix of coconut juice; fermentation temperature 29.5oC with 2.0% Sacchromyces cerevisiae was adequate for coconut juice wine fermentation. Using coconut juice having medicinal and nutritional value as a substrate for wine production, its health benefits can be improved effectively.Keywords: Coconut juice, Wine, Fermentation, Sacchromyces cerevisiae.